New Nanostructured Materials Based on Mesoporous Silica Loaded with Ru(II)/Ru(III) Complexes with Anticancer and Antimicrobial Properties - Gabriela Marinescu; Daniela C. Culita; Teodora Mocanu; Raul-Augustin Mitran; Simona Petrescu; Miruna S. Stan; Mariana C. Chifiriuc; Marcela Popa (MDPI AG, 2023)
A new series of nanostructured materials was obtained by functionalization of SBA-15 mesoporous silica with Ru(II) and Ru(III) complexes bearing Schiff base ligands derived from salicylaldehyde and various amines (1,2-diaminocyclohexane, 1,2-phenylenediamine, ethylenediamine, 1,3-diamino-2-propanol, N,N-dimethylethylenediamine, 2-aminomethyl-pyridine, and 2-(2-aminoethyl)-pyridine). The incorporation of ruthenium complexes into the porous structure of SBA-15 and the structural, morphological, and textural features of the resulting nanostructured materials were investigated by FTIR, XPS, TG/DTA, zeta potential, SEM, and N2 physisorption. The ruthenium complex-loaded SBA-15 silica samples were tested against A549 lung tumor cells and MRC-5 normal lung fibroblasts. A dose-dependent effect was observed, with the highest antitumoral efficiency being recorded for the material containing [Ru(Salen)(PPh3)Cl] (50%/90% decrease in the A549 cells' viability at a concentration of 70 μg/mL/200 μg/mL after 24 h incubation). The other hybrid materials have also shown good cytotoxicity against cancer cells, depending on the ligand included in the ruthenium complex. The antibacterial assay revealed an inhibitory effect for all samples, the most active being those containing [Ru(Salen)(PPh3)Cl], [Ru(Saldiam)(PPh3)Cl], and [Ru(Salaepy)(PPh3)Cl], especially against Staphylococcus aureus and Enterococcus faecalis Gram-positive strains. In conclusion, these nanostructured hybrid materials could represent valuable tools for the development of multi-pharmacologically active compounds with antiproliferative, antibacterial, and antibiofilm activity.